ANALYSIS AND DESIGN OF DATA WAREHOUSE BASED ON SNDIKTI USING DATA WAREHOUSE LIFE CYCLE METHOD AT UNSOED ENGINEERING FACULTY - Nurul Hidayat; Dadang Iskandar; Lasmedi Afuan; Arief Kelik Nugroho; Nandha Arwiansyah (Jurnal Teknik Informatika (Jutif), 2022)
The National Standard for Higher Education (Standar Nasional Pendidikan Tinggi or SNDIKTI) is a standard unit that includes the National Education Standards, plus the Research Standards, and Community Service Standards. Based on the policy in the Regulation of the Minister of Education and Culture (Peraturan Menteri Pendidikan dan Kebudayaan or Permendikbud) No. 3 of 2020 regarding SNDIKTI, Jenderal Soedirman University (Unsoed) Architecture needs to prepare data/ information for analysis based on SNDIKTI 2020. The data is obtained from several internal systems and manual recapitulation within a predetermined period of time. Currently the architecture already has many information systems, but it is still difficult to manage the existing data. So it is important for the architecture to have an important repository to minimize human errors and data inconsistencies. So to perform complex data management, a data warehouse is needed. In this study, the data warehouse design uses the Data Warehouse Life Cycle (DWLC) method with the data warehouse model used is the star schema model. The results of the data warehousing process are in the form of a dashboard, Online Analytical Processing (OLAP), and reports intended for the executives of the Unsoed Faculty of Engineering. The output is presented using a BI (Business Intelligence) tool called Knowage.